2010
DOI: 10.1021/nl102581w
|View full text |Cite
|
Sign up to set email alerts
|

Super Proton Conductive High-Purity Nafion Nanofibers

Abstract: In this paper, we report the high proton conductivity of a single high-purity Nafion nanofiber (1.5 S/cm), which is an order of magnitude higher than the bulk Nafion film ( approximately 0.1 S/cm). We also observe a nanosize effect, where proton conductivity increases sharply with decreasing fiber diameter. X-ray scattering provides a rationale for these findings, where an oriented ionic morphology was observed in the nanofiber in contrast to the isotropic morphology in the bulk film. This work also demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
218
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(236 citation statements)
references
References 24 publications
12
218
0
3
Order By: Relevance
“…This approach involves electrospinning a polymer solution to obtain a nanofiber mat which is afterwards filled with a proton conductive polymer matrix [21][22][23][24][25][26][27][28], although insulating polymers infiltrated into proton conductive nanofibers has also been proposed [29,30]. Interestingly, it has been found that proton conducting nanofibers exponentially increase conductivity with decrease in fiber diameter [25,31]. Higher increment of the proton conductivity is observed along the fiber axis direction than perpendicularly, which is attributed to the preferential orientation of the sulfonated polymeric chains and the consequent alignment of the ionic channels [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…This approach involves electrospinning a polymer solution to obtain a nanofiber mat which is afterwards filled with a proton conductive polymer matrix [21][22][23][24][25][26][27][28], although insulating polymers infiltrated into proton conductive nanofibers has also been proposed [29,30]. Interestingly, it has been found that proton conducting nanofibers exponentially increase conductivity with decrease in fiber diameter [25,31]. Higher increment of the proton conductivity is observed along the fiber axis direction than perpendicularly, which is attributed to the preferential orientation of the sulfonated polymeric chains and the consequent alignment of the ionic channels [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…10 The relatively high proton conductivity under these conditions suggests that GO paper could act as a proton electrolyte in various cells and batteries. [11][12][13][14][15][16] The proton conductivity of the GO paper is lower than that of the conventional Nafion electrolyte, which is usually used at high RH (∼100%), 17,18 while the overall conduction of the GO paper will be similar to that of Nafion if the GO paper is less than a tenth of the thickness of the Nafion.It has been reported that various gases do not pass through the GO paper, even when the GO is very thin (0.1 μm).19 This means thin GO paper is well suited as an electrolyte for the H 2 /O 2 fuel cell, because of the high proton conduction and the H 2 and O 2 gas shielding. Nafion electrolytes must be thick in order to achieve gas shielding (>10 2 μm).…”
mentioning
confidence: 99%
“…To overcome the above problems, new generation electrodes, namely ordered CLs have been proposed [107], developed, widely studied in the laboratory [108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123], and even commercialized [124,125]. In this section, the recent progress in the fabrication of CLs, the efforts to resolve and optimize the microstructure, and new trends in CL designs are reviewed.…”
Section: Catalyst Layermentioning
confidence: 99%
“…Ordered CLs can be broadly divided into three types: (1) ordered carbon phase, such as ordered carbon nanotubes [109,113,120,121], ordered carbon nanofibers [117,137], and ordered mesoporous carbon [112,116,119,122,123]; (2) ordered Nafion ® nanofibers [115,118]; (3) ordered Pt thin film [124,125] or network [110].…”
Section: Ordered Design Of Catalyst Layermentioning
confidence: 99%